Systematic Literature Review: ‘Horenso’ Communication and ‘Kaizen’ Work Culture in Knowledge Management - Kuswara, Galuh Boga; Rofaida, Rofi; Senen, Syamsul Hadi (Business Education Program of Universitas Pendidikan Indonesia, 2024)
This article discusses ‘Horenso’ communication and ‘Kaizen’ work culture in knowledge management in companies and industry. These three variables are thought to be able to encourage a culture of learning and innovation, by utilizing ‘Horenso’ communication and ‘Kaizen’ work culture, so that companies can improve performance and operational efficiency from managed knowledge management. This research method uses the Systematic Literature Review method, with data sources based on the Scopus and Google Scholar databases. The results of this research found that the integration of ‘Horenso’ communication, ‘Kaizen’ work culture, and knowledge management significantly increased effectiveness and efficiency in the Company's performance. ‘Horenso’ communication ensures the efficient flow of information, ‘Kaizen’ drives continuous improvement, and knowledge management facilitates the effective use of knowledge. The combination of the three creates a work environment that values learning and innovation, and requires strong leadership and employee engagement to succeed. This helps companies become more resilient and responsive to dynamic changes.